The Role of Financial Technology (Fintech) in Supporting the Sales of Eco-Friendly Products in Yogyakarta - Elisabeth, Christine Riani (West Science Nature and Technology, 2025)
The increasing demand for environmentally friendly products reflects growing public awareness of environmental sustainability; however, market expansion of such products remains constrained by accessibility and transaction efficiency. Financial technology (fintech) has emerged as an innovative solution that can support sustainable consumption by facilitating faster, easier, and more secure transactions. This study aims to analyze the role of financial technology in supporting the sales of environmentally friendly products in Yogyakarta. A quantitative research approach was employed using survey data collected from 75 respondents, consisting of consumers and business actors involved in environmentally friendly products. Data were gathered through a Likert-scale questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. The results of simple linear regression analysis indicate that fintech has a positive and significant effect on the sales of environmentally friendly products, with a regression coefficient of 0.643 and a significance value below 0.05. The coefficient of determination shows that fintech explains 40.2% of the variance in sales performance. These findings suggest that fintech enhances transaction convenience, improves market accessibility, and encourages purchasing behavior, thereby supporting the commercialization of environmentally friendly products. The study contributes to the literature on fintech and sustainable consumption and provides practical implications for businesses and policymakers in promoting green products through digital financial innovation.